2008
DOI: 10.1213/01.ane.0000298285.39480.28
|View full text |Cite
|
Sign up to set email alerts
|

Management of Lower Limb Complex Regional Pain Syndrome Type 1: An Evaluation of Percutaneous Radiofrequency Thermal Lumbar Sympathectomy Versus Phenol Lumbar Sympathetic Neurolysis—A Pilot Study

Abstract: Based on this pilot study, radiofrequency lumbar sympathectomy may be comparable to phenol lumbar sympathectomy. A larger trial is required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 9 publications
1
50
0
1
Order By: Relevance
“…[1] In a pilot study, percutaneous radiofrequency thermal lumbar sympathectomy has been compared to phenol lumbar sympathetic neurolysis for the treatment of complex regional pain syndrome type 1. [3] In that study, authors have found that both treatment modalities are safe and effective procedures for providing satisfactory pain relief.…”
Section: Introductionmentioning
confidence: 96%
“…[1] In a pilot study, percutaneous radiofrequency thermal lumbar sympathectomy has been compared to phenol lumbar sympathetic neurolysis for the treatment of complex regional pain syndrome type 1. [3] In that study, authors have found that both treatment modalities are safe and effective procedures for providing satisfactory pain relief.…”
Section: Introductionmentioning
confidence: 96%
“…In patients responsive to sympathetic blocks, RFA or phenol neurolysis may provide longer-term symptom control (16,17). RFA may be preferred to phenol based on reports of neuropathic pain symptoms secondary to phenol neurolysis (18). If patients fail to obtain adequate symptom control with the aforementioned treatment, spinal cord/peripheral nerve stimulation or an implantable drug delivery system may be considered (19-21).…”
Section: Case Reportmentioning
confidence: 99%
“…El efecto placebo en pacientes agradecidos y las grandes dosis de anestésico local que provocan una inhibición central de la nocicepción pueden dificultar la interpretación del bloqueo simpático diagnós-tico (30,31).…”
Section: Signos De Eficacia Del Bloqueounclassified